Staffing the Hospitals : An Urgent National Need - Great Britain. Ministry of Labour and National Service. (London : Published for the Minister of health, the Secrerary of State for Scotland and the Minister of labour and national service by H.M.S.O., 1945)
1945 1945 1940s 20 pages 7 and inclination, as her experience grows. Her opportunities for nursing work are not necessarily limited by marriage, and her training and experience will be of direct use to her as a wife and mother. OTHER MEASURES 17. One of the main endeavours will be to secure as last and as widely as events permit, in all hospitals, sanatoria, and other institutions, the adoption of the codes of working conditions set out in the appendices. But that is by no means all there is to do. Many other measures are being taken. 18. Releases from the Services. — General demobilisation from the Armed Forces under Class A is being speeded up and it is hoped that many demobilised men and women with training or experience in nursing, catering or domestic work, will answer the call to further service to the community. A particular appeal is made to all nurses released from the Forces to resume civilian nursing in the various branches of the profession as soon as they possibly can even if this may sometimes involve at the outset accepting a less senior post than they had held in the Forces ; they are urgently wanted. Arrangements have been made for the release from the Women's Auxiliary Services in Class B of up to 2,000 suitable women who volunteer for training as nurses. Arrangements have also been made for the release in Class B of up to 1,000 women with experience in institutional cookery who are prepared to accept employment as hospital cooks. These special measures are additional to those already taken for the release in Class B of women in the Auxiliary Services who have had not less than six months' continuous full-time employment in nursing during the past seven years, and who are not engaged in nursing work in the services, and to the provision for releases in Class B of trained nurses in the nursing services of the Crown who possess highly specialised qualifications which enable them to be regarded as individual specialists. 19. National Reserve of Nurses. — It is proposed to form, as soon as it can be arranged, a new National Reserve of Nurses, similar to the Reserves normally maintained by the Forces. Nurses giving up regular nursing work for marriage or other reasons, will be asked to enrol in this Reserve to be called on for nursing service in any future temporary emergency, such as a serious national epidemic. Full information about the terms of service and the method of joining will be announced shortly. Pending the establishment of this new Reserve, nurses willing to join it can enrol in the Civil Nursing Reserve. 20. Increased Employment of Male Nurses. — Another field for development lies in the increased use of male nurses. There are many men who feel a call to this type of hospital work — and many who have experience of it or experience enabling them to qualify in it — in the Forces and elsewhere. They can help substantially in relieving the present shortage and at the same time find for themselves a satisfying career of service to the community. 21. Wider employment of married women. — Many married women have nursing training and experience, and can give invaluable service if arrangements are made for them to help the hospitals while still retaining their homes and being enabled — as they must be — to live 126/TG/RES/X/1036A/4